Leishmanicidal Effects of Piperlongumine (Piplartine) and Its Putative Metabolites - Moreira, Fernanda de Lima; Riul, Thalita Bachelli; Moreira, Marcela de Lima; Pilon, Alan Cesar; Dias-Baruffi, Marcelo; Araújo, Márcio S. S.; Lopes, Norberto Peporine; de Oliveira, Anderson R. M. (Planta Medica, 2018)
Piperlongumine is an amide alkaloid found in Piperaceae species that shows a broad spectrum of biological properties, including antitumor and antiparasitic activities. Herein, the leishmanicidal effect of piperlongumine and its derivatives produced by a biomimetic model using metalloporphyrins was investigated. The results showed that IC50 values of piperlongumine in promastigote forms of Leishmania infantum and Leishmania amazonensis were 7.9 and 3.3 µM, respectively. The IC50 value of piperlongumine in the intracellular amastigote form of L. amazonensis was 0.4 µM, with a selectivity index of 25. The piperlongumine biomimetic derivatives, Ma and Mb, also showed leishmanicidal effects. We also carried out an in vitro metabolic degradation study showing that Ma is the most stable piperlongumine derivative in rat liver microsome incubations. The results presented here indicate that piperlongumine is a potential leishmanicidal candidate and support the biomimetic approach for development of new antileishmanial derivatives.
Keywords: cyclic amides; piplartine; metalloporphyrin; leishmaniasis; selectivity index; piperlongumine; Piperaceae; analogues